Rancangan Jaringan Komputer di SMK Studi Implementasi Menggunakan Cisco Packet Tracer - Mitro S, Singgih; Dadan Sukma; Hendra Permana (JOURNAL INFORMATION TECHNOLOGY ENGINEERING AND SCIENCE, 2024)
The advancement of computer network technology has rapidly progressed in line with the growing demand for network-based services. A computer network is defined as the connection between two or more computing devices that are linked through transmission media, either wired or wireless. This study aims to analyze and design the computer network infrastructure at SMKN 3 Pandeglang using the Network Development Life Cycle (NDLC) approach. The NDLC methodology comprises six stages: analysis, design, simulation prototype, implementation, monitoring, and management. However, this research focuses on the first three stages, namely analysis, design, and simulation prototype. The results indicate that through the application of network analysis and design using Cisco Packet Tracer, two network design models have been developed for SMKN 3 Pandeglang. These models are ready for implementation, accompanied by an estimation of the required materials and the time needed for the construction of an efficient computer network tailored to the educational institution's needs.